Inhibitory effects of pine nodule extract and its component, SJ-2, on acetylcholine-induced catecholamine secretion and synthesis in bovine adrenal medullary cells - Xiaojia Li; Takafumi Horishita; Yumiko Toyohira; Hui Shao; Jie Bai; Haixia Bo; Xinbo Song; Shin Ishikane; Yukari Yoshinaga; Noriaki Satoh; Masato Tsutsui; Nobuyuki Yanagihara (Elsevier, 2017)
Extract of pine nodules (matsufushi) formed by bark proliferation on the surface of trees of Pinus tabulaeformis or Pinus massoniana has been used as an analgesic for joint pain, rheumatism, neuralgia, dysmenorrhea and other complaints in Chinese traditional medicine. Here we report the effects of matsufushi extract and its components on catecholamine secretion and synthesis in cultured bovine adrenal medullary cells. We found that matsufushi extract (0.0003-0.005%) and its component, SJ-2 (5-hydroxy-3-methoxy-trans-stilbene) (0.3-100 μM), but not the other three, concentration-dependently inhibited catecholamine secretion induced by acetylcholine, a physiological secretagogue. Matsufushi extract (0.0003-0.005%) and SJ-2 (0.3-100 μM) also inhibited 45Ca2+ influx induced by acetylcholine in a concentration-dependent manner, similar to its effect on catecholamine secretion. They also suppressed 14C-catecholamine synthesis and tyrosine hydroxylase activity induced by acetylcholine. In Xenopus oocytes expressing α3β4 nicotinic acetylcholine receptors, matsufushi extract (0.00003-0.001%) and SJ-2 (1-100 μM) directly inhibited the current evoked by acetylcholine. The present findings suggest that SJ-2, as well as matsufushi extract, inhibits acetylcholine-induced catecholamine secretion and synthesis by suppression of nicotinic acetylcholine receptor-ion channels in bovine adrenal medullary cells.